Winter's heart - Jordan, Robert, 1948-2007 (The Wheel of time, 2000)
The epic tale continues as Rand goes into hiding with Min, Perrin's wife is taken captive by the Aiel, Elayne is still trying to gain enough support to take over the throne, and the Daughter of Nine Moons has a confrontation with Queen Tylin.